Intravenous Injection of Clinical Grade Human MSCs after Experimental Stroke: Functional Benefit and Microvascular Effect. Issue 12 (December 2016) - Moisan, Anaïck; Favre, Isabelle; Rome, Claire; De Fraipont, Florence; Grillon, Emmanuelle; Coquery, Nicolas; Mathieu, Hervé; Mayan, Virginie; Naegele, Bernadette; Hommel, Marc; Richard, Marie-Jeanne; Barbier, Emmanuel Luc; et al.
Stroke is the leading cause of disability in adults. Many current clinical trials use intravenous (IV) administration of human bone marrow-derived mesenchymal stem cells (BM-MSCs). This autologous graft requires a delay for ex vivo expansion of cells. We followed microvascular effects and mechanisms of action involved after an IV injection of human BM-MSCs (hBM-MSCs) at a subacute phase of stroke. Rats underwent a transient middle cerebral artery occlusion (MCAo) or a surgery without occlusion (sham) at day 0 (D0). At D8, rats received an IV injection of 3 million hBM-MSCs or PBS-glutamine. In a longitudinal behavioral follow-up, we showed delayed somatosensory and cognitive benefits 4 to 7 weeks after hBM-MSC injection. In a separate longitudinal in vivo magnetic resonance imaging (MRI) study, we observed an enhanced vascular density in the ischemic area 2 and 3 weeks after hBM-MSC injection. Histology and quantitative polymerase chain reaction (qPCR) revealed an overexpression of angiogenic factors such as Ang1 and transforming growth factor-β1 (TGF-β1) at D16 in hBM-MSC-treated MCAo rats compared to PBS-treated MCAo rats. Altogether, delayed IV injection of hBM-MSCs provides functional benefits and increases cerebral angiogenesis in the stroke lesion via a release of endogenous angiogenic factors enhancing the stabilization of newborn vessels. Enhanced angiogenesis could therefore be a means of improving functional recovery after stroke.